Financial Dollarization Equilibria : A Framework for Policy Analysis - Ize, Alain (IMF Working Papers; Working Paper ;, 2005)
Rapidly rising dollarization and numerous related financial crises in recent years have heightened the need for policy action. This paper contributes to the policy debate by presenting a common analytic framework that examines the roots of de facto financial dollarization under different economic environments and analyzes its interplay with monetary and prudential policies. In addition to providing a systematic analysis of the existence, stability, and multiplicity of dollarization equilibria, the paper makes a few novel contributions. In particular, it stresses the key role played by monetary policy endogeneity and identifies the underlying determinants of the peso premium that are responsible for inducing a preference for the dollar in financial transactions.